Long-term Stable Cationic Solid Lipid Nanoparticles for the Enhanced Intracellular Delivery of SMAD3 Antisense Oligonucleotides in Activated Murine Macrophages - Su-Eon Jin; Chong-Kook Kim (Frontiers Media S.A., 2012)
Purpose: Long-term stable cationic solid lipid nanoparticles (cSLNs) were formulated to transfer SMAD3 antisense oligonucleotides (ASOs) into the cells to enhance the intracellular activity of the ASOs. The SMAD3 ASOs were designed to block the inflammatory processes linked to TGFβ/SMAD3 pathway. Methods: The cSLN formulation was prepared by high-pressure homogenization method composed of 1,2-dioleoyl-3-trimethylammonium propane (DOTAP), dioleoylphosphoethanolamine (DOPE), Tween 20, and tricaprin as a solid lipid core (1:1:1:1.67, w/w). The size and the zeta potential of the prepared cSLNs were measured by light scattering. The cSLN/ASO complexes were generated and introduced into the murine macrophage cells. After the treatment of the complexes, the cellular uptake of the complexes was determined by flow cytometry and the intracellular activity of SMAD3 ASOs from the complexes was evaluated by western blotting of SMAD3. In addition, TGFβ1, an upstream molecule of TGFβ/SMAD3 pathway, was monitored by ELISA. Results: The nano-scale sized cSLNs were positively charged and physically stable at 4oC during the storage up to 24 months. The uptake efficiency of the cSLN/ASO complexes into macrophage cells was enhanced up to 80% without cytotoxicity. After the treatment of the cSLN/ASO complexes, SMAD3 as well as TGFβ1 was significantly suppressed based on the SMAD3 ASO activity in the macrophage cells. In addition, the cSLN/ASO complexes prevented the morphological change to dendritic shape in the activated macrophage cells. Conclusion: These results suggest that the cSLNs have a potential to deliver the SMAD3 ASOs to intracellular compartments for the anti-inflammatory effect. The development of this strategy might lead to anti-inflammatory and anti-fibrotic therapies in immunological disorders. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.